The informational value contained in the different types of auditor's opinions: Evidence from Portugal - Paulo Viegascde Carvalho; Joaquim Ferr\~ao; Joaquim Santos Alves; Manuela Sarmento (Cogent Economics & Finance, 2023)
This paper examines the distinct types of modified auditor opinions and the non-compliance with the legal certification of accounts, to assess whether they provide different relevant informational content on the risk of impending bankruptcies. The study also addresses the signalling effects when firms do not comply with disclosure obligations. Controlling for the a priori risk classification, we find that distinct opinion types have dissimilar marginal influences, with a disclaimer of opinion denoting the highest level of risk, followed by the non-compliance with the legal certification of accounts and the issuance of an auditor's adverse opinion. The odds of a firm becoming failed are significantly greater when emphases and reserves are issued by a Big 4 auditor. These findings are based on the evidence of 36,509 firms in Portugal, a country characterized by a proportionately high number of small-sized audited firms and by a lack of independent oversight of auditors, which makes it a relevant setting to analyse.
Keywords: G33; M41; M42; 330; audit qualifications; auditor report; auditor size; bankruptcy prediction; going concern opinions